(3GdHjWQIs ((3YHO GdQMef Hf Ydi GdTGaYi GdcfGfi s)
(3ChdgG (B:s
(3CHhGH GdYdGLGJ (B: (3YdGL GdeTT , Cf jDNP ef HUd GdfQLS , hTF ef SfGe , jOb cd hGMO efgG Ydi MOJI s
(3BNQgG (B:s
(3hRf OQgejf , hJgH Ydjge ef GdRjJ ZeQge , hJWHNge eQgekG hJYGdL HY GdYbhQ hgh BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3QbeJ ajg GdCHhGH HCQbGe gfOjI OGNd OhGFQs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs